The Role of The Social Environment on Civic Education Learning in Growing Social Capital - Linda Wardatul Zadidah; Dasim Budimansyah (Department of Civic Education, 2021)
Indonesia as a multicultural country rich in culture, natural resources and diversity is very difficult to escape from social conflicts. The strong current of globalization has further complicated the problems of Indonesian nationality. One of the factors that cause social conflict in society is the difference in the social environment. The different of social environments make individuals or groups feel the most special from other individuals or groups. Social conflicts that occur due to the influence of differences in the social environment must be resolved in an appropriate manner and with extensive knowledge and sufficient capital such as social capital. Civic education is an important subject that can help grow social capital with â€œthe support provided by the social environment ofâ€ students. This study discusses how the role of the social environment on Civics learning in growing social capital (case study at SMA Negeri 1 Singaparna). â€œThis research uses a qualitative approach with a case study methodâ€. â€œData collection techniquesâ€ using â€œinterviews, observation and documentationâ€. â€œThe results of this studyâ€ suggest that; The social environment of students living in Islamic boarding schools, urban and rural areas has differences in the implementation of Civics learning outcomes and the growth and development of social capital.